Pelaksanaan Putusan Pailit Pengadilan Indonesia Terhadap Pailit yang Melintas Batas Negara - Siti Nurjanah; Ervinna Ervinna (Journal of Judicial Review, 2017)
Along with the development of technology and science, international business transactions conducted by businesses around the world more and more. However, with this increase, the issue of cross-border insolvency often found and become a global problem. To overcome this problem in every country both countries that follow civil law and common law countries adopt and enforce the principle of territoriality principle of universality. Given the importance of cross border enforcement of bankruptcy to protect the rights of creditors and provide legal certainty for the parties concerned in a cross border bankruptcy cases. This study describes clearly and accurately on the implementation of the bankruptcy decision of a foreign court against the bankrupt crossing national borders. This research is a normative juridical law by using comparative law. Data used in the form of secondary data. Data mining is done with literature (library research). After all the data is collected, the data is then processed and analyzed, the qualitative analysis was used to group the data point to the aspects studied. Furthermore, the conclusions drawn related to this research, then described descriptively. Based on this study that the state of Indonesia enacted bankruptcy decision courts of foreign countries in its own territory with the following conditions: to appeal to the judge Indonesia to execute the decision of the bankrupt country in the territory of Indonesia, performing for bankruptcy in the Commercial Court Indonesia to accept the decision handed down by Indonesian courts, Indonesia and the country has a bilateral agreement that allows both countries to resolve cross border insolvency.